The Bretton Woods institutions and the quest for development in Africa - Zekeri Momoh (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
The role of the Bretton Woods Institutions in Africa has been subjected to intense debate in the literature of International Relations. This is so particularly because of the implications of the Bretton Woods Institutions on the political and economic activities in Africa. The data for this study were collected from secondary sources such as textbooks and journal articles while content analysis was used to analyse the data collected. The "False Paradigm Model," propounded by Michael Todaro which is a variant of the Dependency theory, was used for this study. This study revealed mechanisms put in place by the Bretton Woods Institutions in its relationship with African states and it also undertook a critique of the Bretton woods institutional approach to Africa’s development using the false paradigm model. The study further revealed that in spite of experimenting with external development methods and initiatives by the Bretton Wood Institutions, African Economies have not advanced much in terms of development. It implies that African nations must turn within to find it rather than focusing on the Bretton Woods Institutions requirements.